The Role of Moderation of PPh Final PP 55 Year 2022 PPh in Tax Compliance Relations, Financing Access, and Financing Performance of MSMEs In Indonesia - Luntungan, David; Kristinae, Vivy (Neraca Keuangan : Jurnal Ilmiah Akuntansi dan Keuangan, 2026)
MSMEs serve as a fundamental pillar of Indonesia's national economy, contributing significantly to employment absorption and gross domestic product growth. However, persistent challenges surrounding fiscal obligations, capital accessibility, and suboptimal business financial outcomes continue to hinder their sustainable development. Government Regulation No. 55 of 2022 (Peraturan Pemerintah Nomor 55 Tahun 2022), which establishes a simplified final income tax (Pajak Penghasilan Final) rate of 0.5% on gross turnover, represents a strategic policy initiative designed to reduce the administrative and financial burden faced by small business operators. Employing a quantitative research design, this study collected primary data from 50 MSME respondents in Palangka Raya, Central Kalimantan, through structured questionnaires using purposive sampling. Palangka Raya was selected as the research site as it represents the economic center of Central Kalimantan, where MSME activity is concentrated and the implementation of PP 55 of 2022 has been actively monitored by local tax authorities. The collected data were subsequently analyzed using descriptive statistics and moderated multiple regression analysis (MRA) to examine both direct and interaction effects among the studied variables. Prior studies have examined tax compliance and financing access separately, yet the moderating role of PP 55 of 2022 in simultaneously linking both variables to MSME financial performance remains empirically underexplored, particularly at the regional level in Eastern Indonesia. The empirical findings confirm that tax compliance and financing accessibility each exert statistically significant positive effects on MSME financial outcomes (p < 0.05). Furthermore, PP 55 of 2022 functions as a meaningful moderating variable, amplifying the strength of those relationships. These results underscore the importance of synergistic collaboration among regulatory authorities, financial intermediaries, and MSME stakeholders in collectively building a more inclusive, resilient, and sustainable small business ecosystem in Indonesia.